Exploring and Developing Items Measuring Teachers’ Followership Modalities : An Exploratory Factor Analysis Procedure - Lee, Jun Choi; Yeo, Siew Pey; Abdul Halim, Busari (Human Resource Management Academic Research Society, 2021)
The concept of followership has received considerable attention over the past three decades. Good followers play crucial role in determining the success of an organization. However, past followership literature has revealed that there is limited understanding of the dimensions that made up followership modalities, especially in the school context. The purpose of the study was therefore to contribute to the existing literature by performing a thorough validation of the dimensions of Teachers' Followership Modalities through the Exploratory Factor Analysis (EFA) procedure. This study used a cross-sectional survey approach to develop precise measurements for the Teachers’ Followership Modalities construct. A structured questionnaire in Google Form format was used to collect data. The study included 108 randomly selected public secondary school teachers from three districts in Sarawak, namely Kuching, Padawan, and Samarahan. The study revealed that all 20 items adapted and modified from Kelley's (1992) Followership Questionnaire met the EFA procedure's factor loading cut-off point of .60 using IBM-SPSS software version 25.0. Therefore, all 20 items were kept and deemed appropriate for measuring the Teachers' Followership Modalities construct. However, the EFA procedure disclosed 5 components as compared to Kelley’s two-dimensional model. The findings of this study offered a validated and reliable questionnaire to measure Teachers' Followership Modalities among public secondary school teachers in Malaysia. Thus, the Malaysian Ministry of Education which seeks to gain from teachers with good followership modalities will benefit from this research.